Complications of Cirrhosis Evaluation and Management - Keaveny, Andrew P.; Cárdenas, Andrés (Springer International Publishing : Imprint: Springer, 2015)
This volume presents a concise yet comprehensive overview on all facets concerning the complications of cirrhosis. Structured in three sections, the book reviews the natural history of cirrhosis, the diagnostic and predictive tools available to assess the disease, complications, and treatment options such as liver assist devices and transplantation. Topical concerns in the management of patients with cirrhosis are also addressed, including issues pertaining to the delivery of quality care in this patient population. Written by experts in their fields, Complications of Cirrhosis: Evaluation and Management serves as a valuable resource for practitioners and physicians-in-training on the subject of cirrhosis.